Design And Development Of Travel-X: An Ai-Based Tour Travel Application With Smart Itinerary Features And Optimal Travel Experience - Oscar, Gomulia; Bahri, Ronny Samsul (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The rapid advancement of digital technology has significantly transformed tourist behavior, particularly in how they independently plan their trips. AI-based applications such as Travel-X have emerged as modern solutions to automatically generate personalized travel itineraries. This study aims to explore user experiences and perceptions of the Smart Itinerary feature within the Travel-X application, designed to provide efficient, personalized, and optimized travel planning. This research adopts a qualitative descriptive approach, utilizing in-depth interviews with ten informants who have used the Smart Itinerary feature within the past three months. Thematic analysis was employed to identify narrative patterns emerging from user experiences. The findings indicate that the Smart Itinerary feature greatly assists users in creating structured and time-efficient travel plans. While users appreciated the system’s practicality and organization, some noted the need for improved recommendation personalization and flexibility in adjusting plans. Additionally, the study uncovered emotional engagement and user loyalty toward the application. These findings suggest that the success of AI systems in the digital tourism sector relies not only on technical accuracy but also on the system’s ability to understand users' subjective needs.